A Case Report on grade 3 Uterocervical Descent (UCD) with grade 2 cystocele and rectocele (Journal of Pharmaceutical Negative Results, 2022)
Background: Utero-Cervical Descent is part of the pelvic organ prolapse is a group of disease in which organs in the pelvis slip down from their normal position and bulges into the vagina. It includes bladder (cystocele), urethra (urethrocele), both bladder and urethra (cystourethrocele), small intestines (enterocele), rectum (rectocele), sigmoid (sigmoidocele), and the uterus (uterine prolapse). A cystocele is a condition in which supportive tissues around the bladder and anterior vaginal wall weaken and stretch, allowing the bladder and vaginal wall to fall into the vaginal canal. A rectocele is a condition in which the thin wall of tissues that separates the vagina and rectum weakens and allows the posterior vaginal wall to bulge into the vaginal canal. The condition may be asymptomatic at earlier stages but shows significant symptoms at later stages. Case presentation: We are presenting 35 years old G1P1L1A0 female patient who is admitted to the gynecology ward with the primary complaints of feeling something coming out of the vagina along with whitish discharge and lower abdominal pain (hypogastric), and constipation. After a complete physical examination and various other investigations including ultrasonography of the abdomen and pelvis and Per Vaginal examination, she was diagnosed with grade 3 UCD (procidentia) with grade 2 cystocele and rectocele. The patient has undergone a surgical procedure known as exploring vaginal hysterectomy with vaginal wall repair and treated with analgesic, antibiotics, and proton-pump-inhibitors. After treatment patients’ condition improves and symptoms such as bulging and protruding mass in the vaginal canal, whitish vaginal discharge, and constipation were relieved after surgery. Conclusion: A pelvic organ prolapse is a condition in which the bladder bulges through the anterior vaginal wall into the vaginal canal and the rectum bulges through the posterior vaginal wall into the vaginal canal. Females are more likely to experience this condition after menopause. Treatment involves an interdisciplinary surgical approach and appropriate management of existing medical conditions, to restore functionality by treating pelvic organ prolapse and improving symptoms.